Experiential learning in African Planning Schools: reflections on the Association of African Planning Schools (AAPS) case study project - Odendaal, Nancy (Revista Brasileira de Estudos Urbanos e Regionais, 2013)
Abstract: In 2009 the AAPS embarked on a project entitled ‘Revitalising Planning Education’, funded by the Rockefeller Foundation. This project is currently in its second phase. Its primary aim is to move planning away from its control-focused origins (still practiced in many parts of the Continent) and reinvent it as a practice that is supportive of the poor in African cities. An entry point for doing this practically was formulated in the form of a second project that focused on case study research and documentation. Using the idea of phronesis developed by Bent Flyvbjerg as a point of departure, the Association facilitated a series of workshops and publications on the method, as a tool for teaching and knowledge production. "is paper reflects on the pedagogical dimension in particular, in reflecting on the project’s outcomes and its implications for graduate education, whilst also drawing on recent collaborative studio projects run in conjunction with Slum Dwellers International in reflecting on possible modalities for best achieving experiential learning.